Urban China: Toward Efficient, Inclusive, and Sustainable Urbanization - TheWorldBank (World Bank, 2015)
In the last 30 years, China?s record economic growth lifted half a billion people out of poverty, with rapid urbanization providing abundant labor, cheap land, and good infrastructure. While China has avoided some of the common ills of urbanization, strains are showing as inefficient land development leads to urban sprawl and ghost towns, pollution threatens people?s health, and farmland and water resources are becoming scarce. With China?s urban population projected to rise to about one billion ? or close to 70 percent of the country?s population ? by 2030, China?s leaders are seeking a more coordinated urbanization process.